Patterns of Changes in C-Reactive Protein (CRP) in Patients Performed Intestinal Anastomosis Resection - Embong Wicaksono; Sarup Singh (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2018)
ABSTRACT Introduction. C-reactive protein (CRP) is used as a marker of intestinal anastomosis leakage, its short half-life can be used as a predictor of intestinal anastomosis leakage. This study aimed to determine the pattern of increased preoperative and postoperative CRP in all patients undergoing bowel grafting. Methods. This was an observational analytic study with a prospective cohort design of 20 patients undergoing intestinal anastomosis. Comparative analysis using the unpaired t-test, man whitney test and fisher test. Results. The mean preoperative CRP serum up to the sixth postoperative day in the leakage group was higher than non-leakage, but there were no significant differences between the two groups (ppreop = 0.852; pPOH1 = 0.791; pPOH2 = 0.634; pPOH3 = 0.507; pPOH4 = 0.534; 0.507; pPOH5 = 0.506; pPOH6 = 0.595). CRP cut-off values >170 mg / L on the second postoperative day had the maximum sensitivity (67%) and specificity (65%) in knowing the risk of anastomotic leakage. Conclusion. An increase in CRP levels up to the third postoperative day is a marker of anastomotic leakage. CRP cut-off values> 170 mg / L on the second postoperative day have maximum sensitivity and specificity.